COVID-19-associated vasculitis and vasculopathy - Becker, Richard C. (Journal of thrombosis and thrombolysis, 2020)
The COVID-19 pandemic now totaling 13,000,000 cases and over 571,000 deaths has continued to teach the medical, scientific and lay communities about viral infectious disease in the modern era. Among the many lessons learned for the medical community is the potential for transmissibility and host infectivity of the SARS–CoV-2 virus. Moreover, it has become clear that the virus can affect any organ including the circulatory system, directly via either tissue tropism or indirectly stemming from inflammatory responses in the form of innate immunity, leukocyte debris such as cell-free DNA and histones and RNA viral particles. The following review considers COVID-19-associated vasculitis and vasculopathy as a defining feature of a virus-induced systemic disease with acute, subacute and potential chronic health implications.